THE DEVELOPMENT OF BLENDED LEARNING BASED ON HANDPHONE FOR COMPUTER SYSTEM SUBJECT ON XI GRADE OF SMKN 1 BENGKULU CITY - Wibawa, Basuki; ., Paidi (Humanities & Social Sciences Reviews, 2019)
Purpose of Study: Education has an important role to improve the quality of human resources that made the younger generations could develop their potential optimally. Vocational High School (SMK) is one of the educational institutions that has prepared their graduates to enter the working world. One of the compulsory programs in Vocational High School is the students were carried out on the fieldwork practices (PKL). To provide learning access for students as long as they stayed in the industry area, so it was necessary to give learning on blended learning by using handphone as a learning media. In order to get students’ learning outcomes be maximized, so the development of this learning should be done by applying Research and Development patterns that were adapted from The Steps of System Approach Model of Educational Research and Development (R & D), Fourth Edition and Seventh Edition by Borg and Gall. Blended learning models that would be developed are Norman Vaughan and Flipped Classroom Models. Learning materials were developed are computer system subject. The measurement of result development was done by the formative evaluation that consisted of one to one evaluation with expert, one to one evaluation with learner, small group and field trial. Methodology: The methodology that was conducted is stages of learning model adopted from Model of The Steps of System Approach Model of Educational Reseach and Development (R & D), Fourth Edition and Seventh Edition by Borg and Gall. The blended learning model that will be developed is the Norman Vaughan model and Flipped Classroom Model. (Helena Gillespie et.all, 2007) Results: Stages of learning model development that was adopted from Model of The Steps of System Approach Model of Educational Reseach and Development (R & D), Fourth Edition and Seventh Edition by Borg and Gall. The blended Vaughan model and Flipped Classroom Model. Stages of development process as follows:1) Data and Information Collecting, 2) Identity Instructional Goal, 3) Conduct instructional Analyze, 4) Analyze Learners and Contexts, 5) Write Performance Objectives, 6) Develop AssessmentInstrument, 7) Develop Instructional Strategy, 8 Develop and Select Instructional Materials, 9) Revise Instruction, 10) Design and Conduct Formative Evaluation of Instruction (Gall et all). Implications/Applications: Development of blended learning based on handphone was appropriate to be used in learning at XI grade of SMK. It was caused that students of XI grade have followed the practice of field work for about 3 months, as long as the students followed the practice of fieldwork, it meant that the learning process was still being applied by using handphone media and learning outcomes showed that there was an improvement in learning outcomes.